Determinants of Islamic financial literacy towards retirement planning - Abdillahi, Abdifatah Mohamoud (2015)
This study attempts to investigate the determinants of Islamic financial literacy towards retirement planning. The survey involved 230 Muslim respondents among the University Utara Malaysia, College of Business (UUM COB) staffs. All the data were analyzed through Statistical Package for Social Science (SPSS) by conducting statistical method namely, Independent Samples T-Test, Analysis of Variance (ANOVA), Pearson Correlation and Multiple Linear Regression analysis to archive the objectives of this research. The result of this study shows that the level of retirement planning of the respondents is high. The findings also revealed that there are four determinants that significantly influence towards retirement planning. Among them are goal clarity, knowledge of financial planning for retirement planning, income and gender, the result on gender shows that the male respondents have higher retirement planning compare to females.